2003
DOI: 10.5694/j.1326-5377.2003.tb05393.x
|View full text |Cite
|
Sign up to set email alerts
|

Older women's sexuality

Abstract: SEXUAL PROBLEMS are relatively common in women, occurring in up to 43% of younger women 1 and increasing with age. 2 These result from an interaction of biological, psychological and social factors. 3 As the population in the Western world ages, there is more attention focused on quality-of-life issues as they affect older people. (In Australia, older people are defined as those aged over 65 years. 4 ) The proportion of older people who remain sexually active varies considerably with age, sex, marital status a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Moreover, we used a cross-sectional design, thus our results do not imply causation; additionally, to limit the scope of this study, the interview protocols covered several, but not all factors that could be related to sexual desire and fantasies. For instance, acculturation was not measured, and neither were other variables often related to women’s sexuality in later life, such as masturbation or sexual activity at a younger age (Yee and Sundquist 2003). Another limitation concerns the assumptions and interpretations that the present authors have made about the sexual culture of older Mexican-American women, as it is evident in the way in which some questions were formulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we used a cross-sectional design, thus our results do not imply causation; additionally, to limit the scope of this study, the interview protocols covered several, but not all factors that could be related to sexual desire and fantasies. For instance, acculturation was not measured, and neither were other variables often related to women’s sexuality in later life, such as masturbation or sexual activity at a younger age (Yee and Sundquist 2003). Another limitation concerns the assumptions and interpretations that the present authors have made about the sexual culture of older Mexican-American women, as it is evident in the way in which some questions were formulated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, researchers have discovered that ageing does not necessarily precipitate decreased longing for sexual intimacy (National Council on the Aging 1998; Laumann, Paik, and Glasser 2002). In fact, older women’s sexual satisfaction is highly related to overall well-being, life satisfaction, and physical health (Yee and Sundquist 2003). To better understand the sexual needs and behaviours of minority ethnic older women in particular, researchers must acknowledge that these women traditionally place a strong emphasis on cultural prescriptions and norms (Phinney and Flores 2002).…”
mentioning
confidence: 99%
“…Testosterone deficiency and decreased secretion of estrogen may result in vaginal dryness and painful intercourse, atrophic skin changes, shrinkage and atrophy of the clitoris and vagina, diminished sensation, urogenital prolapse, and urinary incontinence. Other empirical results documented in the literature include reduction in skin's sensitivity to touch, reduced olfactory epithelium's sensitivity to smell, loss of muscle bulk and bone mass, loss of sense of well-being, cognitive slowing, and loss of concentration [1, 12]. Researchers have reported that hormone replacement therapy (HRT) could improve quality of life for some women [13].…”
Section: Studies On Biopsychosocial Factors Affecting Older Women'mentioning
confidence: 99%
“…Continual sexual activity carries numerous health benefits throughout the life span: because sexual intimacy impacts sexual desire necessary for ongoing healthy sexual interactions in human relationships, problems in any area of the sexual experience should be addressed as part of a holistic health assessment (as discussed by Yee and Sundquist [1]). Sexuality and older women are issues, however, that are typically dichotomized rather than considered a naturally occurring combination to be explored and nurtured in their intersection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation